Toward Understanding the B[e] Phenomenon. II. New Galactic FS CMa Stars - Miroshnichenko, A. S. (2007)
FS CMa stars form a group of objects with the B[e] phenomenon that were previously known as unclassified B[e] stars or B[e] stars with warm dust (B[e]WD) until recently. They exhibit strong emission-line spectra and strong IR excesses, most likely due to recently formed circumstellar dust. These properties have been suggested to be due to ongoing or recent rapid mass exchange in binary systems with hot primaries and various types of secondaries. The first paper of this series reported an analysis of the available information about previously known Galactic objects with the B[e] phenomenon, the initial selection of the FS CMa group objects, and a qualitative explanation of their properties. This paper reports the results of our new search for more FS CMa objects in the IRAS Point Source Catalog. We present new photometric criteria for identifying FS CMa stars as well as the first results of our observations of nine new FS CMa group members. With this addition, the FS CMa group has now 40 members, becoming the largest among the dust-forming hot star groups. We also present nine objects with no evidence for the B[e] phenomenon, but with newly discovered spectral line emission and /or strong IR excesses.